Inventory Management Evaluation and Inventory Forecast Using EOQ - Rorim Panday; Dovina Navanti (Syntax Literate, 2021)
The fashion industry that is gamis in Indonesia is growing rapidly because the majority of the population is Moslem. Elzatta is a company that does business on Moslem clothing, one of its products is the gamis. The company is experiencing problems with stockpiling in warehouses, because of models that were not sold, as well as outdated models. With the accumulation of products in warehouses in 2017 and 2018, many products will be damaged. For this reason, the company runs a buy one get one business strategy and sells products at low prices. As a result, the company suffered a substantial loss. For this reason, it is necessary to evaluate the inventory management that has been carried out using the EOQ model. For 2019, it is necessary to plan the number of products to be sold and apply the EOQ model. The results of evaluations in 2017 and 2018, by using EOQ the company could save 64.78% for 2017 and 63.40% for 2018. Whereas for 2019, after forecasting the number of sales using the seasonal model, sales projections are similar to the number of sales in the previous years, so that the number of products needed for a single order is 1364 pcs.